Situation Report: Bulgaria, 30 June 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Todor Zhivkov's Visit to Algeria Ends Heavy Rains and Hail Damage Homes and Crops Bulgarian-Hungarian Co-operation Agreement Signed Comings and Goings Bulgarian Minister in Belgrade Bulgarian-North Korean Co-Operation Bulgarian Education Ministry Group in East Germany Soviet Minister in Sofia Moscow Delegation in Sofia Czechoslovak Ideological Workers in Sofia Moroccan Delegation in Sofia